2023
DOI: 10.3390/ijms24043903
|View full text |Cite
|
Sign up to set email alerts
|

A New Concept of Enhancing the Anticancer Activity of Manganese Terpyridine Complex by Oxygen-Containing Substituent Modification

Abstract: Eleven manganese 4′-substituted-2,2′:6′,2″-terpyridine complexes (1a–1c and 2a–2h) with three non-oxygen-containing substituents (L1a–L1c: phenyl, naphthalen-2-yl and naphthalen-1-yl, L1a–L1c) and eight oxygen-containing substituents (L2a–L2h: 4-hydroxyl-phenyl, 3-hydroxyl-phenyl, 2-hydroxyl-phenyl, 4-methoxyl-phenyl, 4-carboxyl-phenyl, 4-(methylsulfonyl)phenyl, 4-nitrophenyl and furan-2-yl) were prepared and characterized by IR, elemental analysis or single crystal X-ray diffraction. In vitro data demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Copper (II) and Zinc (II) terpyridine conjugated complexes prepared by Velugula et al induced apoptosis in MCF‐7 and HeLa cells, whose activities were comparable with cisplatin 16 . Manganese complexes with terpyridine ligands acted as DNA intercalators, which coincided with their anticancer activity on MCF‐7, Bel‐7402, A549, Eca‐109, and HeLa cells 21 . Our research group has also reported potential anticancer activity of cobalt (III) bitpy complex against MCF‐7 and HeLa cells 22 .…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Copper (II) and Zinc (II) terpyridine conjugated complexes prepared by Velugula et al induced apoptosis in MCF‐7 and HeLa cells, whose activities were comparable with cisplatin 16 . Manganese complexes with terpyridine ligands acted as DNA intercalators, which coincided with their anticancer activity on MCF‐7, Bel‐7402, A549, Eca‐109, and HeLa cells 21 . Our research group has also reported potential anticancer activity of cobalt (III) bitpy complex against MCF‐7 and HeLa cells 22 .…”
Section: Introductionmentioning
confidence: 87%
“…16 Manganese complexes with terpyridine ligands acted as DNA intercalators, which coincided with their anticancer activity on MCF-7, Bel-7402, A549, Eca-109, and HeLa cells. 21 Our research group has also reported potential anticancer activity of cobalt (III) bitpy complex against MCF-7 and HeLa cells. 22 Albeit numerous terpyridine complexes have shown good activity against cancer cells, the factors that oversee their action and target are still obscure.…”
Section: Introductionmentioning
confidence: 95%